Cinética da secreção de insulina, concentração de Ca2+ e expressão de proteínas da maquinaria de exocitose da insulina em ilhotas pancreáticas de ratas submetidas à restrição protéica desde a vida intra uterina ou recuperadas a partir do desmame - Marin, Bianca Karine (2012)
We investigated the kinetics of glucose-induced insulin secretion and its relationship with calcium [Ca2+]i and the expression of protein from exocytotic machinery in islets from recovered pregnant and long-term protein-restricted pregnant rats. Isolated islets from control-fed or protein-restricted pregnant and non-pregnant (CP; CNP and LPP; LPNP, respectively) rats, from fetal to adult life, and in protein-restricted rats that were recovered after weaning (RP; RNP) were evaluated. In the RP and CP groups, glucose-induced biphasic insulin secretion increased, with a rapid first-phase release after exposure to high levels of glucose, followed by a decrease, and then an increase during the second phase. Islets from LPP rats exhibited the monophasic pattern with a small peak of insulin release, followed by maintenance of the constant values. Insulin secretion during the first phase was similar in the RP and RNP groups as well as in the LPP and LPNP groups but was higher in the CP group than in the CNP group. The amounts of [Ca2+]i in islets from the protein-restricted groups were lower than those in the control groups, and both were lower in relation to the RP and RNP groups. SNAP-25 was increased in islets from pregnant rats independently of their nutritional status, and syntaxin-1 content was reduced in islets from the RP rats in relation to the RNP rats. VAMP2 content was similar among the groups. Thus, protein restriction during intrauterine life and lactation increased [Ca2+]I, but impaired the classical first phase of insulin release during pregnancy, due at least in part to reduced Sintaxin-1 expression.